PENGARUH RASIO KEUANGAN DAN PENURUNAN TARIF PAJAK TERHADAP PEMBAYARAN DIVIDEN - Andinie Fatimah (JURNAL EKOBIS DEWANTARA, 2018)
The aim of this study is to find out whether financial ratios and decreases in tax rates affect the payment of dividends in goods and consumption industry sector companies that are listed on the Indonesia Stock Exchange. This study uses secondary data with the documentation method in the form of the company's annual financial statements. The research period was conducted from 2012 - 2016. The research approach used is a quantitative approach with purposive sampling method. Of the 40 population companies of goods and consumption industry sectors listed on the Indonesia Stock Exchange a sample of 12 companies was taken with a period of 5 years. The results of this study state that earnings per share and a decrease in tax rates affect the dividend payout ratio, and the current ratio and return on assets have no effect on dividend payout ratio.